Pembinaan Agama melalui Kajian Dakwah Roblox dalam Kehidupan Remaja - Asty Azahra; Mutiara Tania (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2025)
​Social media digitalization triggers a social anxiety crisis known as Fear of Missing Out (FOMO) among youth, necessitating adaptive religious guidance innovations. This descriptive qualitative study aims to analyze the effectiveness of cyber dawah on the Roblox platform via the detikINET YouTube channel in addressing youth mental health issues. Observation was conducted on the interactions of three teenage participants (Raisya, Anarasya, Surya) and a preacher (Ustadz Jojo). The results indicate that the study mechanism is interactively structured through the "Masjid Al-Blok" virtual map, gaming activities, and account anonymity, providing psychological comfort. Internalizing the "FOMO Dunia vs FOMO Akhirat" material through fostering qana'ah successfully reorients teenagers' material ambitions toward spiritual deeds. In conclusion, the integration of cyber dawah and the preacher’s noble attitude significantly serves as a mental healing instrument to stabilize teenagers' unstable emotional turbulence in the digital era.